TAPE TECHNOLOGY: APPLICATIONS AND INNOVATIONS IN LOGISTICS AND PACKAGING - da Costa, Gentil Marciano (LUMEN ET VIRTUS, 2023)
Adhesive tape has become a crucial component in modern logistics and packaging systems, evolving from a basic sealing tool to a multifunctional material with applications in security, sustainability, automation, and branding. This article explores the diverse roles and innovations of adhesive tape, emphasizing pressure-sensitive adhesives, tamper-evident technologies, reinforced materials, and environmentally sustainable alternatives. Drawing from academic research, it highlights the tape’s contribution to operational efficiency, supply chain integrity, and packaging optimization in response to evolving global demands. The analysis demonstrates how advancements in adhesive systems are shaping the future of packaging logistics. These innovations not only support high-performance requirements but also align with corporate goals for environmental responsibility. As e-commerce and global trade continue to expand, adhesive tape technologies are expected to play an increasingly strategic role across packaging sectors.